2007
DOI: 10.1128/jb.00382-07
|View full text |Cite
|
Sign up to set email alerts
|

The Extracytoplasmic Function-Type Sigma Factor SigM of Corynebacterium glutamicum ATCC 13032 Is Involved in Transcription of Disulfide Stress-Related Genes

Abstract: The gene for the extracytoplasmic function (ECF) sigma factor SigM was deleted from the chromosome of the gram-positive soil bacterium Corynebacterium glutamicum to elucidate the role of the SigM protein in the regulation of gene expression. Comparative DNA microarray hybridizations of the C. glutamicum wild type and sigM-deficient mutant C. glutamicum DN1 revealed 23 genes with enhanced expression in the sigM-proficient strain, encoding functions in the assembly of iron-sulfur clusters (suf operon), thioredox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 70 publications
0
61
0
Order By: Relevance
“…Following chelation of ferrous iron, B. breve UCC2003 evokes a stress-like response demonstrated by the upregulation of the chaperone GroEL (Bbr_1364). 38,39 Iron-chelation was also shown to upregulate transcription of nrdF (Bbr_1898), encoding a predicted ribonucleotide reductase. The latter enzyme is known in E. coli to catalyze the reduction of ribonucleotides to deoxyribonucleotides as a first step in the pathway for DNA replication, where synthesis of nrd mRNA increases when DNA synthesis is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Following chelation of ferrous iron, B. breve UCC2003 evokes a stress-like response demonstrated by the upregulation of the chaperone GroEL (Bbr_1364). 38,39 Iron-chelation was also shown to upregulate transcription of nrdF (Bbr_1898), encoding a predicted ribonucleotide reductase. The latter enzyme is known in E. coli to catalyze the reduction of ribonucleotides to deoxyribonucleotides as a first step in the pathway for DNA replication, where synthesis of nrd mRNA increases when DNA synthesis is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptional start site was assumed when at least three of the 10 clones showed the same 5Ј-end and when the other clones contained nonidentical shorter transcripts. The TSS were found to be located 57,196,32, and 45 bp upstream of the proposed translational start sites of cg1150, rosR, cg1848, and cg2329, respectively.…”
Section: Identification Of Transcriptional Start Sites Of Rosr Targetmentioning
confidence: 99%
“…6B). Expression of the trxB1 gene was induced by diamide in the QorRC17S-expressing strain as shown previously by Nakunst et al (15), indicating that cells were subjected to disulfide stress (Fig. 6C).…”
Section: Cys-17 Of Qorr Is Required For Regulation Of Qor2 Expressionmentioning
confidence: 80%
“…4C), but the transcript levels of qor2 and qorR did not respond to H 2 O 2 (data not shown). It has been shown that the sigM transcript level is also increased by diamide but not by H 2 O 2 (15). As C. glutamicum is highly resistant to H 2 O 2 (15), H 2 O 2 is supposed to be unable to induce C. glutamicum oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation